Insight in the Recent Application of Polyphenols From Biomass - Yan, Bowen; Chen, Zhefan Stephen; Hu, Yingying; Yong, Qiang (Frontiers in Bioengineering and Biotechnology, 2021)
Biomass polyphenols are bio-active macromolecules with distinct chemical structures in a variety of biomass. In recent years, the study of biomass polyphenols and their application in food and medicine fields has become a research hotspot, which predominantly focuses on the preparation, purification, structural identifications, and measurements of biological activities. Many studies describe methodologies for extraction and application of polyphenols, but comprehensive work to review its physiological activities like drugs and health products are lacking. This paper comprehensively unlocks the bioactivities of antioxidant, antibacterial, antitumor, anticancer, neuroprotection, control of blood sugar, regulation of blood fat, and promotion of gastrointestinal health functions of polyphenols from different biomass sources. This review will serve as an illuminating resource for the global scientific community, especially for those who are actively working to promote the advances of the polyphenols research field.